IJCM_316A: Prevalence of work-related musculoskeletal disorders among school teachers in Ernakulam district, Kerala - Joy Sarah; Menon Vishnu b (Wolters Kluwer Medknow Publications, 2024)
Background: Work-related Musculoskeletal disorders (WRMSD) stand as a prevalent and significant occupational health issue within the teaching profession. Despite being overlooked for an extended period, there has been a growing level of concern about this issue in recent years. Objectives: 1. To estimate the prevalence of work-related musculoskeletal disorders among school teachers in Ernakulam district, Kerala. 2. To determine the risk factors associated with work-related musculoskeletal disorders. Methodology: A cross sectional study was conducted among 114 school teachers in Ernakulam district selected by multistage cluster sampling. A structured interview schedule was used to assess the sociodemographic and occupational characteristics. To investigate the musculoskeletal disorders, they were interviewed with the modified Nordic questionnaire. The data was entered in MS excel and analysis was done using SPSS version 21.0. Results: Mean age (SD) of the participants was 43.25 (7.56) years. The prevalence of Work-related Musculoskeletal disorders at any part of the body over the past 12 months among teachers was 52.6%. Knee pain (41.6%) was the most prevalent WRMSD followed by ankle (38.3%) pain. Commonly perceived risk factor was standing for prolonged periods (81.6%). Stair climbing was found to be the most difficult Activity of Daily Living affected due to the symptoms (55%). Calcium/Vitamin D supplements, intake of calcium rich diet and body mass index were significantly associated with WRMSD. Conclusion: The results highlighted the crucial need to follow ergonomic guidelines in order to reduce the strain on the musculoskeletal system experienced by teachers.